Electronic key information summaries can highlight patients' wishes out of hours. Issue 3 (1st September 2016) - Finucane, Anne; Tapsfield, Julia; Hall, Charlie; Lunan, Carey; McCutheon, Hazel; McLoughlin, Peter; Rhee, Joel
Abstract : Introduction: Electronic Key Information Summaries (KIS) are shared electronic patient records widely used throughout Scotland. 1 These allow selected parts of the GP patient record to be routinely shared with healthcare professionals across settings. The KIS may contain vital information to support out of hours palliative care decision-making, such as patient preferences for place of care, DNAPCR status and anticipatory medicines. Aim: To identify when different information pertinent to out of hours palliative care decision-making was serially recorded within the KIS for patients who died with cancer, organ failure or frailty and/or dementia. Method: A retrospective review of the primary care notes of deceased patients across nine general practices in Lothian was conducted in 2014. Sudden and unexpected deaths were excluded. Data were collected on the type and timing (number of weeks before death) of information recorded in the KIS. Results: We analysed 605 patient notes. A KIS was shared for patients with organ failure 22 weeks before death (Mdn = 22, IQR = 10–31), and for those with frailty and/or dementia, 20 weeks before death (Mdn = 20, IQR = 8–34). For patients with cancer, KIS's were commenced later (Mdn = 14, IQR = 6–27). Most patients with a KIS had information on anticipatory care, preferred place of care and DNACPR shared during the last month of life. Information on anticipatory medicines was shared two weeks before death (Mdn = 2, IQR = 1–6). Conclusion: Electronic key information summaries facilitate the timely documentation and sharing of patient information that is vital to support out of hours decision-making and prevent inappropriate hospital admissions. Reference: Tapsfield J, Hall C, Lunan C, McCutheon H, McLoughlin P, Rhee J, Rus A, Spiller J, Finucane A, Murray SA. Many people in Scotland now benefit from anticipatory care before they die: an after death analysis and interviews with general practitioners. BMJ Supportive and Palliative Care 2016. doi:10.1136/bmjspcare-2015-001014